The Effect of Using Videos and Photovoice on the Students' Achievement in Writing Explanation Text - Ifa Amalia Anwar (Graduate Program, University of Islam Malang, 2021)
This study aims to explore the effectiveness of using videos and photovoice on the students’ achievement in writing Explanation text. It is a quasi-experimental design which involves 70 students of MAN 1 Banyuwangi in 2020/2021 academic year. XI MIPA 1 as the control group and XI MIPA 2 as the experimental group. These two groups were proved on the same level of writing ability by the score of pre-test. There were six meeting in this research, a meeting for pre-test, four meetings for the treatment through E-Learning Madrasah, and a meeting for post-test. The data obtained were analyzed by using independent t-test formula. The result showed that the t-value =-2.729, p =.008 and the results indicated that there is significant difference after having treatment by using videos and photovoice since p =.008 is less than 0.05. Based on the result of data analysis, the eleventh grade students of MAN 1 Banyuwangi who were taught by using videos and photovoice achieve better score on writing Explanation text than those who were taught by using PowerPoint.Keywords: videos, photovoice, explanation text